Assessment of safe injection practices and disposal methods among nursing personnel at health care centres of Hoskote - Rural Bengaluru, India - Shabana Achapatira Ganesh; Nikhitha Raghunath; Shilpashree Komarla Balaji (Wolters Kluwer Medknow Publications, 2015)
Introduction: Unsafe injection practices are commonplace in developing country health settings. These unsafe practices predispose the health care workers to various risks and also facilitate transmission of an array of diseases to the health care professionals and the community. Aim: To assess safe injection practices and disposal methods among nursing personnel at health care centres. Materials and Methods: A hospital based cross-sectional study was conducted among 86 nurses at health care centres of rural Bengaluru. Data were collected using a 20 item questionnaire. Along with demographic details questions regarding knowledge, practices, and disposal methods were included. Data were subjected to descriptive analysis. Results: The study population consisted of 89.5% female nurses and 10.5% were males. Among them only 46.5% were protected by hepatitis B vaccination. During the last 12 months 25.6% nurses had accidental needlestick injury (NSI). The subjects who practiced squeezing out blood at the puncture site and washed their hands immediately after NSI were 51.2%. A total of 82.6% of the subjects were of the opinion that human immunodeficiency virus/AIDS was the only disease transmitted by unsafe injection. Regarding the methods of disposal of used needles and syringes in their hospital 89.5% had no information of the same. Conclusions: There is a great disparity between the ideal and practiced methods among the nursing personnel. There is an immediate need to reinforce the importance of safe practices periodically through training and motivation on safe injection practices and its disposal.